2022
DOI: 10.23960/jbm.v18i0.314
|View full text |Cite
|
Sign up to set email alerts
|

Job Performance dan Job Satisfaction Wartawan Sebagai Dampak Job Stress Di Masa Pandemi COVID-19

Abstract: This study aimed to analyze the effect of job stress on job performance and job satisfaction by mediating work engagement. This study uses Job Stress as the independent variable, Job Performance and Job Satisfaction as the dependent variables, and Work Engagement as the mediating variable. Data collection from 311 print and online media journalists in Jakarta. The data collection technique in this study used purposive sampling, and the research instrument used a questionnaire sent via Google Form. Data analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In addition, Zahra et al's research (2022)) states that over time a person will become more involved in his work because the focus is on completing his tasks, and tasks that are considered complicated provide additional motivation for workers. Research findings by Agustina et al (2022), Zahra et al (2022), andInoue et al (2014) support the findings in this study and explain that workload can motivate workers to stay motivated. This finding also confirms that one form of stress is eustress (Selye, 1977).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, Zahra et al's research (2022)) states that over time a person will become more involved in his work because the focus is on completing his tasks, and tasks that are considered complicated provide additional motivation for workers. Research findings by Agustina et al (2022), Zahra et al (2022), andInoue et al (2014) support the findings in this study and explain that workload can motivate workers to stay motivated. This finding also confirms that one form of stress is eustress (Selye, 1977).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies prove that job stress and work engagement can be positively related. Research by Agustina et al (2022) found that job stress has a positive effect on work engagement because workers can focus on their work and feel overly excited. In addition, Zahra et al's research (2022)) states that over time a person will become more involved in his work because the focus is on completing his tasks, and tasks that are considered complicated provide additional motivation for workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job satisfaction has a direct impact on job performance by mediating the demographic and job characteristics. Work satisfaction studies show a favorable association between job satisfaction and job performance [76,78]. The current study's findings also indicated that satisfied workers perform better than unsatisfied workers in terms of quality of work, quantity of work, job knowledge, initiative, creativity, cooperativeness, undependability, and personal development.…”
Section: Discussionsupporting
confidence: 58%
“…This study consisted of 51 subordinates and 28 supervisors, and the study found that job satisfaction is related to employee performance because exultant employees are more likely to be concerned about the tasks at hand, work quickly, produce error-and omission-free work, be willing to take on more responsibility, and perform at their best. Employee job satisfaction, according to Agustina et al [76], is a key factor in organizational performance. Some of these studies' conclusions showed a high correlation between worker job satisfaction and job performance [77].…”
Section: Job Satisfaction and Job Performancementioning
confidence: 99%